Some Characterization Results of Nonlocal Special Random Impulsive Differential Evolution Equations - Jose, Sayooj Aby; Tom, Ashitha; Abinaya, S.; Yukunthorn, Weera (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we present existence and uniqueness of special random impulsive differential evolution equations with nonlocal condition in Hilbert spaces. Moreover we study the stability results for the same evolution equations. Existence and uniqueness results are proved using Banach fixed point theorem where as stability results using fixed point approach and semi group theory. Finally we give some applications of the nonlocal impulsive differential equations as well as evolution equations, which shows the importance of our theoretical results.